COLLECTIONS AND THE SHAPING OF LITERARY PREFERENCES IN MEXICO (Andamios, Revista de Investigación Social, 2009)
This paper discusses the influence of editing and publishing on the readers’ literary preferences, either through collections as reading programs (in case of the institutions interested in the diffusion of culture) or as reading offers (in case of the businesses that participate in the cultural marketing in Mexico.) Both editing processes share a cultural history, a cultural patrimony and political strategies for growing and strengthening.
Keywords: editing and publishing; literary preferences; reading; culture diffusion; cultural consumption; collections